Investigation of Self‐Discharge Behavior on Electrical Double‐Layer Capacitors by Hybrid Mechanism Simulation. Issue 4 (23rd February 2022) - Fan, Lingling; Yang, Chongyang; An, Zhongxun; Chen, Yigang
Abstract : Self‐discharge (SD) of electrical double‐layer capacitors (EDLCs) has become an important issue that will cause voltage decay and energy loss. Herein, the SD profiles of EDLCs with a three‐electrode test cell (Ag/Ag + as reference electrode) in 1 mol L −1 tetraethylammonium tetrafluoroborate/acetonitrile are examined, coupled with the potential record of the positive and negative electrodes. The results show that the negative electrode should be mainly responsible for the SD process in the capacitors regardless of the mass ratio of the electrodes. The hybrid mechanism model, combined with the activation‐controlled faradaic process, diffusion process, and ohmic leakage process, can be utilized to explain the SD mechanism of the cell, positive electrode, and negative electrode showing that the main contribution arises from the effect of activation‐controlled faradaic process. The initial voltage is the driving force of the faradaic process in SD for high energy state, and its contribution decreases with the decrease of initial voltage. The higher temperature exacerbates the voltage variation from both faradaic and diffusion process, while the contribution proportion from the diffusion process is more significant with temperature. Abstract : The self‐discharge (SD) behavior of electrical double‐layer capacitors (EDLCs) in organic electrolyte can be analyzed by the hybrid mechanism simulation. The hybrid mechanism simulation can distinguish the contribution of each mechanism of the positive and negative electrodes, and research the SD mechanism influenced by the initial voltage (1.5–2.7 V) and the temperature (15–35 °C).